TMEM9 promotes intestinal tumorigenesis through vacuolar-ATPase-activated Wnt/β-catenin signalling. Issue 12 (December 2018) - Jung, Youn-Sang; Jun, Sohee; Kim, Moon; Lee, Sung; Suh, Han; Lien, Esther; Jung, Hae-Yun; Lee, Sunhye; Zhang, Jie; Yang, Jung-In; Ji, Hong; Wu, Ji; et al.
Abstract Vesicular acidification and trafficking are associated with various cellular processes. However, their pathologic relevance to cancer remains elusive. We identified transmembrane protein 9 (TMEM9) as a vesicular acidification regulator. TMEM9 is highly upregulated in colorectal cancer. Proteomic and biochemical analyses show that TMEM9 binds to and facilitates assembly of vacuolar-ATPase (v-ATPase), a vacuolar proton pump, resulting in enhanced vesicular acidification and trafficking. TMEM9-v-ATPase hyperactivates Wnt/β-catenin signalling via lysosomal degradation of adenomatous polyposis coli (APC). Moreover, TMEM9 transactivated by β-catenin functions as a positive feedback regulator of Wnt signalling in colorectal cancer. Genetic ablation of TMEM9 inhibits colorectal cancer cell proliferation in vitro, ex vivo and in vivo mouse models. Moreover, administration of v-ATPase inhibitors suppresses intestinal tumorigenesis ofAPC mouse models and human patient-derived xenografts. Our results reveal the unexpected roles of TMEM9-controlled vesicular acidification in hyperactivating Wnt/β-catenin signalling through APC degradation, and propose the blockade of TMEM9-v-ATPase as a viable option for colorectal cancer treatment. Jung et al demonstrate that TMEM9 facilitates vacuolar-ATPase assembly to enhance vesicular acidification, thereby promoting activation of Wnt signalling and development of colorectal cancer.